The Use of Age Management to Professional Activation of the Elderly = Wykorzystanie zarządzania wiekiem w obszarze aktywizacji zawodowej osób starszych - Niewiadomska, Anna (Zielona Góra: Faculty of Economics and Management Press)
The increase in interest in the topic of aging is associated ? to some extent ? with the currently unavoidable demographic changes. On the one hand, life expectancy increases, on the other hand, fertility rates fall. As a consequence the proportion of younger generations is reduced, and the share of older generations. A disturbing fact has been the low level of economic activity of the elderly, among others in Europe for many years. The reasons for this are complex.
Keywords: zarządzanie wiekiem; starzenie się społeczeństwa; aktywność zawodowa; age management; ageing society; professional activity